Adaptive fault tolerant control and thruster fault reconstruction for autonomous underwater vehicle. (1st May 2018) - Liu, Xing; Zhang, Mingjun; Yao, Feng
Abstract: This paper investigates adaptive fault tolerant control and fault reconstruction problem for AUV subject to ocean current disturbance and modelling uncertainty. At first, a virtual closed-loop system based adaptive fault tolerant control method is developed. In this method, the constructed virtual closed-loop system is mainly used to deal with the influence of the initial tracking error in an ideal environment and avoid the serious chattering phenomenon in control output. Then with respect to fault reconstruction in the framework of fault tolerant control, an improved second-order sliding mode observer is constructed to estimate the thruster fault effect. The feedback of the developed observer consists of different functions of the estimation errors, including fractional function, signature function and integral function etc. Furthermore, the stability analysis is given based on Lyapunov theory. Finally, a series of simulations are performed on an over-actuated AUV for different desired trajectories and different types of thruster faults under the condition of the simulated ocean current environment. The comparative simulation results demonstrate the effectiveness and feasibility of the new design. Highlights: A virtual closed-loop system based adaptive fault tolerant control method is proposed. An improved second-order sliding mode observer is constructed to estimate the thruster fault effect. Results from comparative simulation studies are given.